2018
DOI: 10.1002/asia.201800324
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Driven Symmetry Change for Terbium(III) Bis(porphyrinato) Double‐Decker Complexes by the Azimuthal Rotation of the Porphyrin Macrocycles

Abstract: Molecular structures for three oxidation forms (anion, radical, and cation) of terbium(III) bis(porphyrinato) double-decker complexes have been systematically studied. We found that the redox state controls the azimuthal rotation angle (φ) between the two porphyrin macrocycles. For [Tb (tpp) ] (tpp: tetraphenylporphyrinato, n=-1, 0, and +1), φ decreases at each stage of the oxidation process. The decrease in φ is due to the higher steric repulsion between the phenyl rings on the porphyrin macrocycle and the β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…More recently, Yamashita et al. have observed structural changes in Por double‐decker complexes induced by ligand oxidation using single‐crystal X‐ray (SXRD) measurements and have shown that ligand oxidation induces axial compression, which has been supported by theoretical calculations . Moreover, the axial compression in Pc double‐decker complexes induced by oxidation has been investigated by using solution NMR spectroscopy .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…More recently, Yamashita et al. have observed structural changes in Por double‐decker complexes induced by ligand oxidation using single‐crystal X‐ray (SXRD) measurements and have shown that ligand oxidation induces axial compression, which has been supported by theoretical calculations . Moreover, the axial compression in Pc double‐decker complexes induced by oxidation has been investigated by using solution NMR spectroscopy .…”
Section: Introductionmentioning
confidence: 91%
“…[27][28][29][30] More recently,Y amashita et al have observed structural changes in Pord ouble-decker complexes induced by ligand oxidation using single-crystal Xray (SXRD) measurements and have shown that ligand oxidation induces axial compression, which has been supported by theoretical calculations. [31] Moreover, the axial compression in Pc double-decker complexes induced by oxidation has been investigated by using solutionN MR spectroscopy. [32] The conformational changes, especially ligand rotation,i nd oubledecker complexes have been directly observed [33,34] and controlled using as canning electron microscope (STM) and scanning electron spectroscopy (STS).…”
Section: Introductionmentioning
confidence: 99%
“…The eight ethyl groups on the porphyrin macrocycle of H 2 OEP seem to have a much smaller steric effect since the f angle is equal to 451 for n = À1 and 0 and decreases to only 361 for n = +1. 254 In the series [Ln(Nc)(TBPP)], where H 2 TBPP is meso-tetra(4-tbutylphenyl)porphyrin, three quasi-reversible, one-electron oxidation and one reduction steps are revealed by cyclic voltammetry in methylene chloride at ambient temperature. 166 A second reduction could not be detected owing to solvent breakdown.…”
Section: Porphyrinato Lanthanide Complexesmentioning
confidence: 99%
“…The anionic complex 2 shows a near square antiprism (SAP) coordination, having ϕ of 41° (Figure b), whereas 1 and 3 have distorted SAP structures with smaller ϕ (33° and 40°) (Figures a and 2c). This dependence of the ϕ on the chemical states of the complexes is similar to those of previously reported Tb(TPP) 2 complexes, which indicates the validity of the structural identification ,…”
Section: Figurementioning
confidence: 99%
“…Monoradical [(TPP)Tb(TPP)] . shows near IR (1340 nm) absorption because of the promotion of an electron from a filled bonding orbital to the half‐filled anti‐bonding orbital ,. In 1 and 1′ , probably because of the combination of the similar electron promotion with a larger delocalization of the π‐electron of FP, an IR optical energy gap is formed.…”
Section: Figurementioning
confidence: 99%